Ningmitai capsules have anti-inflammatory and pain-relieving effects in the chronic prostatitis/chronic pelvic pain syndrome mouse model through systemic immunity - Liu, Hanchao; Wang, Zhenqing; Xie, Qigen; Chi, Ani; Li, Yanqing; Dai, Jian; Zhang, Min; Deng, Chunhua; Liu, Guihua (Frontiers in Pharmacology, 2022)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) seriously affects the physical and mental health of about 90% of male. Due to the complex and unclear etiology, the current treatment methods are still controversial and the efficacy is unstable. At present, most relevant researchers believe that this kind of prostatitis is an autoimmune inflammation. As the essence of traditional Chinese medicine (TCM), Chinese herbal is an emerging treatment for treating inflammation and immune disease. In this experiment, we investigated the effect of Ningmitai capsules (a kind of TCM widely used to treat male lower urinary tract inflammation and pain) on CP/CPPS in no obesity diabetes-experimental autoimmune prostatitis (NOD-EAP) mice. First of all, we found that quercetin, one of the main components of Ningmitai capsules, could reduce the secretion of CCL2 protein by inhibiting the MAPK pathway by bioinformatic analysis in ETCM database. In animal experiments, it was found that after Ningmitai treatment, the inflammation of the prostate in mice was alleviated, the expression of the pain factor CCL2 and MAPK pathway were down-regulated, and the activation of the inflammatory pathway NF-κB and STAT3 pathway was reduced. Pelvic pain and inflammation were relieved in the EAP mice. Due to the existence of the blood-prostate barrier, the drug may not fully directly reach the prostate and exert its effects locally. However, we found that after Ningmitai treatment, the pro-inflammatory CD11b+Ly6Chigh immune cells in the spleen, bloodstream of systemic immunity and the prostate of local immunity were reduced. And the infiltration of CD11b+ immune cells was reduced in spleen and prostate. This suggested that Ningmitai can treat CP/CPPS by affecting systemic and local immunity through CCL2-MAPK pathway.